Planejamento e gestão ambiental em bacias hidrográficas: análise da fragilidade ambiental do Rio Caeté - DIAS, Filipe Gomes (2019)
The knowledge of the potentialities and limitations of the natural systems is fundamental so that the anthropic actions undertaken in these are according to their characteristics, dynamics and functionalities. The use of Geotechnologies, integrated to the systemic analysis of the landscape, is increasingly indispensable in the studies related to environmental problems. Thus, this work aims to elaborate the Environmental Fragility map of the Caeté Hydrographic Basin based on the methodological proposal of Crepani et al. (2001) as a subsidy instrument for decision-making in the planning and environmental management of the basin's territory. We constructed the base maps of the geoenvironmental units of the Caeté river basin as: Declivity, Soil Types, Geology, Geomorphology and Land Use. The result of the mapping of the Environmental Fragility of the Caeté River Basin presented a very low level, demonstrating a certain dynamic balance of the geoenvironmental components of the area landscape. However, we emphasize the need for deepening and on-site treatment of other socio-environmental and economic variables that the methodology used can not contemplate for a broader analysis.